Homophily as a driver in the creation of interpersonal relationships and knowledge sharing - Karhunen, Marjo (My University, 2013)
It has been found that homophily has a significant impact on kind of interpersonal ties that individuals establish and the quality of these ties influences knowledge sharing behaviour. According to previous research similarity drives social capital. Strong ties are facilitators of effective knowledge sharing when weak ties are better sources for new information. The purpose of this study is to investigate connection between homophily, social capital and interpersonal knowledge sharing. The study will identify homophily based characteristics and investigate further on which type of homophily seems to matter the most for development of social capital and how along these ties knowledge is shared. The research is based on qualitative study where nine semi-structured interviews were used as a means of data collection. The respondents were mostly women working in a MNC. The results of the study show that common characteristics able creation of the first connection between individuals but these characteristics loose their importance if the relationship develops further. Common values and attitudes are the most important factors driving the development of social capital. According to study relationship where cognitive and relational social capital is high are the most important informal channels for knowledge sharing.
Keywords: Knowledge sharing; interpersonal relationships; homophily; social capital; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|